Knowledge is Power: An Analysis of Counseling Professionals’ Medicare Policy Proficiency - Matthew C. Fullen; Jordan Westcott; Julianna Williams (Journal for Social Action in Counseling and Psychology)
This study examines counseling professionals’ knowledge concerning the Medicare program and related advocacy efforts. American Counseling Association members (N = 5,097) answered a series of true-false questions that were intended to measure proficiency in two areas: Medicare policy and the counseling profession’s advocacy for provider eligibility. Statistical analyses indicated that members have a wide range of Medicare knowledge. A significant difference in advocacy history knowledge was found when comparing counselor educators, practicing counselors, doctoral students, and master’s students. However, no differences in policy knowledge were present among these groups. Implications for the counseling profession and counselor training are discussed.